Comparison of the laparoscopic versus open live donor nephrectomy: an overview of surgical complications and outcome - Fonouni, Hamidreza; Mehrabi, Arianeb; Golriz, Mohammad; Zeier, Martin; Müller, Beat P.; Schemmer, Peter; Werner, Jens (Langenbeck's archives of surgery, 2014)
Kidney transplantation (KTx) is considered to be the treatment of choice for end stage renal disease. One of the most challenging dilemmas in KTx is the shortage of suitable organs. The live donor nephrectomy is considered a unique operation performed on healthy donors, which provides a superior outcome in the recipients.